PENGARUH MOTIVASI BELAJAR, KREATIVITAS BELAJAR, DAN KOMPETENSI GURU TERHADAP PRESTASI BELAJAR AKIDAH AKHLAK SISWA - Muhammad Farih Alfaaza; Didit Darmawan (IAIN Bone, 2025)
Education plays a vital role in shaping students’ character and moral values, particularly through the Aqidah Akhlak subject, which focuses on instilling Islamic teachings. This study aims to examine the influence of learning motivation, learning creativity, and teacher competence on students’ academic achievement at MTsN 4 Surabaya City. This research uses a quantitative method with a survey approach, and the instrument used is a questionnaire.The population consisted of 723 students, with a sample of 173 eighth-grade students selected using purposive sampling. Data were analyzed using multiple linear regression to determine the effect of the independent variables on the dependent variable. The findings reveal that learning motivation, learning creativity, and teacher competence each have a positive and significant impact on students’ achievement in Aqidah Akhlak. Learning motivation and creativity contribute to enhancing students’ understanding, while teacher competence plays an important role in creating a conducive learning environment. Based on these results, it is recommended that teachers continue to develop their competencies and implement innovative and interactive teaching methods to foster student motivation. Schools are also encouraged to support teacher quality improvement and provide facilities that stimulate students’ creativity and learning motivation.